UbiComp 2006: Ubiquitous Computing 8th International Conference, UbiComp 2006, Orange County, CA, USA, September 17-21, 2006, Proceedings - Dourish, Paul.; Friday, Adrian; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2006)
Fifteen years after the publication of Weiser’s seminal paper in Scientific American, ubiquitous computing is a large, thriving field of academic research and commercial innovation. The proceedings of the 8th International Conference on Ubiquitous C- puting reflect the strength, diversity and vigor of the research program that Weiser initiated. We hope that you will find much in the papers contained herein to stimulate new and exciting work as we reach forward toward ubiquitous computing together. The location of the conference, in Orange County, California, was particularly - posite given recent directions in the field. A Pacific Rim location linked the conf- ence to last year’s venue in Tokyo, Japan, and provided an appropriate space to reflect on the different implementations and visions of ubiquitous computing in d- ferent parts of the world. Two significant elements of local industry – the software industry and the entertainment industry – reflect concerns heavily represented in - cent research in ubiquitous computing, with mobile and ubiquitous gaming, for - stance, an obvious link. The unique metropolitan setting of the Los Angeles region provided a useful setting in which to develop research agendas in urban computing. Finally, while there are no papers in the proceedings on surfing-based Ubicomp, the cultural focus on healthy lifestyles in Southern California relates to concerns with aging and health as important application areas for ubiquitous computing technologies and solutions.
A Quantitative Method for Revealing and Comparing Places in the Home -- Principles of Smart Home Control -- Historical Analysis: Using the Past to Design the Future -- Extending Authoring Tools for Location-Aware Applications with an Infrastructure Visualization Layer -- Automated Generation of Basic Custom Sensor-Based Embedded Computing Systems Guided by End-User Optimization Criteria -- An Experimental Comparison of Physical Mobile Interaction Techniques: Touching, Pointing and Scanning -- An Exploratory Study of How Older Women Use Mobile Phones -- Farther Than You May Think: An Empirical Investigation of the Proximity of Users to Their Mobile Phones -- No More SMS from Jesus: Ubicomp, Religion and Techno-spiritual Practices -- Scribe4Me: Evaluating a Mobile Sound Transcription Tool for the Deaf -- SenseCam: A Retrospective Memory Aid -- Development of a Privacy Addendum for Open Source Licenses: Value Sensitive Design in Industry -- Mobility Detection Using Everyday GSM Traces -- Practical Metropolitan-Scale Positioning for GSM Phones -- Predestination: Inferring Destinations from Partial Trajectories -- Fish’n’Steps: Encouraging Physical Activity with an Interactive Computer Game -- Hitchers: Designing for Cellular Positioning -- Embedding Behavior Modification Strategies into a Consumer Electronic Device: A Case Study -- Instrumenting the City: Developing Methods for Observing and Understanding the Digital Cityscape -- Voting with Your Feet: An Investigative Study of the Relationship Between Place Visit Behavior and Preference -- Lo-Fi Matchmaking: A Study of Social Pairing for Backpackers -- Experiences from Real-World Deployment of Context-Aware Technologies in a Hospital Environment -- Doing Community: Co-construction of Meaning and Use with Interactive Information Kiosks -- Moving on from Weiser’s Vision of Calm Computing: Engaging UbiComp Experiences -- Ferret: RFID Localization for Pervasive Multimedia -- PowerLine Positioning: A Practical Sub-Room-Level Indoor Location System for Domestic Use -- UbiREAL: Realistic Smartspace Simulator for Systematic Testing -- Instant Matchmaking: Simple and Secure Integrated Ubiquitous Computing Environments -- A Wirelessly-Powered Platform for Sensing and Computation -- Automated Application-Specific Tuning of Parameterized Sensor-Based Embedded System Building Blocks.
Keywords: User interfaces (Computer systems).; Computer communication systems; Software engineering; Operating systems (Computers).; Application software; Computers and civilization; User Interfaces and Human Computer Interaction; Computer Communication Networks; Software Engineering; Operating Systems; Information Systems Applications (incl. Internet).; Computers and Society